Estimation of the efficiency of partial case of heat and mass transfer processes between heat pumps and moving substance: Part 3 - Kshevetsky, O.S.; Orletskyi, O.V. (Journal of Thermoelectricity, 2019)
A theoretical model for evaluating the efficiency of the partial case of heat and mass transfer processes between a moving substance and thermoelectric heat pumps with their heat exchange parts, in which the moving substance (or at least part of this moving substance) is brought into thermal contact with heat absorbing and heat dissipating heat exchangers , which can operate in modes that may differ from the mode of maximum energy efficiency, in particular, taking into account the amounts of materials required for the manufacture of these thermoelectric heat pumps. The results of the corresponding theoretical estimation are given. Bibl. 9, Tabl. 1, Fig. 2.